Competitive Strategy and Performance in Mexico, Peru, and the United States - Parnell, John A. (2010)
This paper compares competitive strategy-performance relationships in Mexico, Peru, and the USA. 334 managers in the USA, 398 in Mexico, and 314 in Peru completed surveys. An innovative strategy orientation was positively associated with performance satisfaction in all 3 nations. The link between low cost strategy orientation and performance was negative in Mexico and positive in the USA. Mexican firms were the most innovative and Peruvian the most cost-oriented. Top managers in Mexico considered their firms’ strategies less innovative and more cost-oriented than did middle and lower level managers. Top managers in Peru considered their firms’ strategies more cost-oriented than did middle and lower level managers. The U.S. sample showed no significant strategy differences across management levels.